Effect of coconut milk-rice ratios and cooling-reheating cycles in amylose-lipid complex of buras: Indonesian traditional rice cake - Pranoto, Yudi; Sabrina, A'isyah Mutiara; Prawira, Muhammad Aditya (jurnal1, 2025)
Resistant starch (RS), particularly RS5, has attracted considerable scientific interest due to its potential health-promoting effects, including reduced risk of degenerative diseases. However, research on RS5 in commonly consumed food products, like Buras, a traditional Indonesian dish, remains limited. Buras is made by cooking rice with coconut milk, which contains starch and lipids that can interact to form amylose-lipid complexes. The present study evaluates the effect of varying rice-to-coconut milk ratios and multiple cooling-reheating cycles on the formation of RS5 in Buras. The experimental method involved preparing Buras with four different rice-to-coconut milk ratios: P1 (1:1), P2 (1:2), P3 (1:3), and P4 (1:4). After cooking, Buras were subjected to multiple cooling-heating cycles, where they were cooled at 4°C for 6 hours and reheated in a steamer for 10 minutes. Control samples (S0) underwent no cooling-reheating cycles. Several parameters were measured, including amylose content, RS, starch digestibility, physicochemical characteristics, and complexing index (CI). Results indicated that the P2 ratio (1:2) produced the highest RS (7%) and significantly reduced starch hydrolysis. The amylose-lipid complex in Buras was confirmed through XRD peaks at 13°, 17°, and 20°, as well as FTIR ester group signals. Additionally, multiple cooling-reheating cycles further increased RS content while reducing starch digestibility. The findings suggest that the rice-to-coconut milk ratio and post-cooking processing are crucial for optimizing RS5 formation in Buras, offering potential health benefits and improving its nutritional profile. This research contributes to modernizing traditional recipes while maintaining their cultural significance.